2013
DOI: 10.1007/s10815-013-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced protein C Global assay level in infertile women prior to IVF-ET treatment

Abstract: Purpose In the last few years more robust evidence is emerging to point out at an increased rate of prematurity and low birth weight in singleton pregnancies following ART. Whether this increased rate is related to ART practice or to infertility per se, is still an open question. Our aim in this study was to explore this question by evaluating Protein C (ProC) Global assay in infertile women before ART treatment. Methods A cohort of 95 unselected and consecutive infertile women, eligible for ART, was prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
3
4
1
Order By: Relevance
“…The abnormally low protein C global levels were independent of patient age and BMI, as well as infertility duration and etiology, and these findings are in agreement with Younis et al [19]. The duration and cause of infertility did not seem to affect the results either.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The abnormally low protein C global levels were independent of patient age and BMI, as well as infertility duration and etiology, and these findings are in agreement with Younis et al [19]. The duration and cause of infertility did not seem to affect the results either.…”
Section: Discussionsupporting
confidence: 90%
“…It also verifies findings in a subsequent study by the same group [19 ]which reported that levels of protein C global assay were much more decreased in infertile women eligible for ART compared to fertile women who conceived naturally. The authors concluded that, before ART treatment, decreased protein C global levels are encountered in women with infertility.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many studies addressed the relation of hereditary thrombophilia and infertility especially cases related to assisted reproduction and repeated IVF failure. Reduced protein C global assay level was found in infertile women prior to assisted reproduction treatment, a finding suggesting unique anticoagulation protein C pathway in infertile compared to fertile women [17]. It has been established that the majority of placental vascular complications associated with thrombophilias during pregnancy have been related to the protein C pathway [10,18].…”
Section: Discussionmentioning
confidence: 99%